PENCIPTAAN KURSI TERAS GAYA MODERN DENGAN KOMBINASI BAHAN KAYU DAN STAINLESS - Komda Saharja; Muhammad rizqi auliansyah; Kukuh Dwi Wijanarko (SULUH: Jurnal Seni Desain Budaya, 2021)
The use of two-dimensional (2D) animation as a medium for nconveying messages and information has been widely used. The message or invitation can be applied in various media which are very easy to access in the digital era like now. The theme that the author raises in this animated video is about the benefits of coffee as a media for soft selling promotion for Cafe Killiney Indonesia. This is done with the aim of marketing the Killiney Indonesia brand through educational media and can have a positive impact on the audience. The method used in making this 2-dimensional animation is by conducting observation and research through various reading media such as articles, news, newspapers, and other media information media. Then, the finished 2-dimensional animation will result in a video that is displayed on various social media so that it iseasier for many people to access.